Legal Response to Oil Pollution in the Maritime Environment: A Comparative Analysis of Nigeria, United Kingdom and the United States - Tamuno, Paul S. (ABUAD Law Journal, 2021)
This article undertakes a comparative analysis of the legal response to oil pollution in the maritime environment in Nigeria, the United Kingdom and the United States. Major oil spills in these three states are examined with the aim of highlighting how each state responded to the pollution. In Nigeria, oil spills that are examined include: Texaco’sFuniwa-5 oil well spill of 1980 and the Mobil Qua-Iboe oil spillage of 1998. As regards the United Kingdom, the Torrey Canyon incident and other spills are examined. For the United States, the Ixtoc 1 spill of 1979, the Exxon Valdez spill of 1989 and the Deepwater Horizon spill of 2010 are examined. These spills were often due to accidents and negligence during oil drilling and transportation. The United Kingdom and the United States had more robust legislation and policies that spelt out in advance how companies were to respond to oil spills. They also had effective mechanisms for the implementation and enforcement of the response to oil spills. This was the case even in situations, such as the Torrey Canyon incident, in which the oil spills was from a vessel transporting crude oil in the international waters. In Nigeria, legislation on oil spills were often outdated andin conflict with each other. They were also poorly implemented due to inter alia inadequate funds, lack of political will on the part of the government and the fact that the Nigerian government is in Joint Venture agreements with the Multinational oil companies.